2019
DOI: 10.1186/s12935-019-0924-9
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of circFLNA contributes to laryngeal squamous cell carcinoma migration by circFLNA–miR-486-3p-FLNA axis

Abstract: Background Accumulating evidence shows that circular RNAs (circRNAs) plays vital roles in tumor progression. However, the biological functions of circRNAs in laryngeal squamous cell carcinoma (LSCC) metastasis is still unclear. Methods qRT-PCR was used to detect circFLNA, miRNAs and FLNA mRNA expression. Transwell assay and western blot were performed to evaluate cell migration ability and to detect FLNA, MMP2 and MLK1 protein expression, respectively. RNA pull-down ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Accumulating studies have shown that miRNAs are implicated in LSCC development, including proliferation, apoptosis, migration and invasion [8][9][10]. Our previous study has confirmed that miR-486 is involved in LSCC cell migration by targeting FLNA [11]. Moreover, miR-370, which functions as a tumor suppressor, participates in LSCC cell growth by inducing FOXM1 expression [12].…”
mentioning
confidence: 81%
“…Accumulating studies have shown that miRNAs are implicated in LSCC development, including proliferation, apoptosis, migration and invasion [8][9][10]. Our previous study has confirmed that miR-486 is involved in LSCC cell migration by targeting FLNA [11]. Moreover, miR-370, which functions as a tumor suppressor, participates in LSCC cell growth by inducing FOXM1 expression [12].…”
mentioning
confidence: 81%
“…Lending further support to this notion, a recent study has also discovered an OSCC-associated, splicing factor-derived circRNA, named circUHRF1, and demonstrated its involvement in tumorigenesis [30]. Interestingly, a circRNA (circFLNA) derived from another filamin family gene, filamin A, was reported to impact the migration of the laryngeal squamous cell carcinoma, which is related histologically and anatomically to oral cancer [31]. Collectively, these key findings underscore the critical role of transcriptomic alterations underlying oral cancer progression, and also augment their potential value regarding the detection, prevention, and treatment of this disease.…”
Section: Discussionmentioning
confidence: 85%
“…However, a study by Zhang et al, showed that miR-103 is upregulated in adriamycin-resistant cells ( 51 ). miR-486-3p could act as a tumor-suppressive miRNA in several cancers ( 52 54 ). In our study, pre-miR-124s (miR-124-1, miR-124-2 and miR-124-3) were upregulated in early recurrence B-ALL, and miR-124-3p was predicted to target the gene IFI44L .…”
Section: Discussionmentioning
confidence: 99%